Cultivating a thriving agricultural sector: Unveiling the drivers of farmer participation in agricultural development interventions in Ghana - Magdalene Aidoo; Stephen Prah; Irene Serwaa Asante; Charles Kwame Sackey; Bright Owusu Asante (Social Sciences and Humanities Open)
Participation in agricultural development interventions has not been encouraging among smallholder farmers in developing countries. However, agricultural productivity has been low and characterized by a lack of access to improved production technologies and agricultural services. Using a random sample of 477 maize farmers, this paper examines the drivers of participation in an integrated delivery model of the smallholder inclusive productivity and market access (SIPMA) interventions in the Bono East region of Ghana. We utilized three models – binary probit, multivariate probit and generalized Poisson to achieve the objectives of this paper. Our results showed that socioeconomic (education, maize farming experience, farm plots, and land ownership) and institutional (extension contact, FBO membership, and innovative platform membership) factors played a significant role in the decision and number of SIPMA interventions farmer participated in. We found that socioeconomic characteristics had diminutive influence on participating in multiple SIPMA interventions, whereas institutional factors had major effect in participating in multiple SIPMA interventions. Strategies for increasing participation in agricultural programmes such as the SIPMA interventions for enhancing productivity, income, and food security of farmers should target experienced and educated farmers who already belong to innovation platforms or farmer groups, having extension contact, and own their farmlands.